Updates in paleodermatology: revisiting ancient skin disease through modern lenses - Wang, Vera; Adams, Derrick (International Journal of Research in Dermatology, 2025)
Paleodermatology is the study of ancient skin diseases via preserved human remains. This review builds upon Dr. Eve Lowenstein’s foundational 2004 work on paleodermatoses, summarizing new discoveries, techniques, and insights gained about infectious disease, neoplasms, and tattoos over the past twenty years. This review also addresses the controversial identification of melanoma in ancient Incan remains. Much of what has been analyzed about past skin conditions have been misconceptions based upon our modern biases and assumptions, so we highlight these cases as well as provide new analyses. This provides insight into not only historical epidemics and lifestyles, but also the relationship between modern disease and our environments.